LANDSCAPING IN SULAYMANIYAH CITY'S LUXURIOUS HOTELS BASED ON GUESTS' NEEDS AND ENVIRONMENTAL CONDITIONS - SHARBAZHERY, ALI O. M. SHARBAZHERY (Journal of Duhok University, 2023)
The research was conducted in three luxurious hotels in Sulaymaniyah City: Grand Millenium, Titanic, and High Crest. From July 15th, 2022 to July 10th, 2023, to study the reality of Landscaping in those Luxurious Hotels in terms of their areas, components, and recreational activities that they offer to their visitors.The data for the study was obtained through four methods: personal observation, architectural design analysis, interviews with hotel management, and questionnaire distributed to hotel guests.The research obtained several results and conclusions, the most important of which are: The most significant interest in the three hotels is in the entrance gardens and car parking, then the back gardens. The reason for this is due to the high prices of land in the city, only a small space was allocated for gardens and more importance was given to the hotel building. There was no interior, wall, and roof gardens in the three samples. Nonetheless, 99% of respondents confirmed their wish to stay in a hotel with gardens, and more than 90% of guests prefer the presence of water in the gardens in the form of fountains, waterfalls, and swimming pools. Furthermore, the city's environment is characterized by an extremely harsh climate, with variations between summer (47°C) and winter (-20°C) temperatures reaching 65-70°C, necessitating appropriate garden designs and plants that resist harsh weather. Various recommendations were developed to improve the design of hotel gardens in the city of Sulaymaniyah based on the study's findings and conclusions, with many design proposals for external and internal gardens, as well as hotel walls and roofs.